PENERAPAN TERAPI REBUSAN AIR DAUN BINAHONG UNTUK MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM DI RUANG CILAMAYA BARU RSUD KARAWANG - Yuli Erlina; Dina Hartini; Rendi Fauzi (Bajang Institute, 2024)
Perineal wounds are a common problem experienced by postpartum mothers, especially those with normal deliveries with episiotomy. These wounds can cause pain, discomfort, and risk infection if not cared for optimally. One non-pharmacological method to accelerate wound healing is using a decoction of binahong leaves (Anredera cordifolia), which contain saponins, flavonoids, and ascorbic acid, which function as antibacterials and accelerate tissue regeneration. This community service activity aims to improve the knowledge and skills of health workers and postpartum mothers in applying binahong leaf decoction therapy to accelerate perineal wound healing. The activity method was carried out through socialization, demonstrations, and direct practice. Participants were 15 nurses/midwives and 10 postpartum mothers in the Cilamaya Baru ward at Karawang Regional Hospital. The activity included educational counseling, practical training on making binahong leaf decoction, and a simulation of how to use it on perineal wounds. Evaluation was carried out using a pre-posttest of knowledge and observation of skills. The results of the activity showed an increase in participants' knowledge from 65% to 93% and an increase in skills from 55% to 90%. Participants stated that this therapy is easy to perform, the ingredients are readily available, and it has no side effects. The socialization of binahong leaf decoction therapy effectively increased the knowledge and skills of nurses, midwives, and postpartum mothers in accelerating the healing of perineal wounds naturally and safely.